The Effects of The Geomorphology and Geologic Parent Materials on the Natural Environment Assessment in the Burdur-Golhisar Basin, SW Anatolia - Atalay, Ibrahim; Altunbas, Sevda; Siler, Muzaffer (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Burdur-Golhisar basin which is located in the western part of Lakes Region of Mediterranean region is found between the Menderes metamorphic masse and the eastern continuation of Taurus Mountain range. The present-day topography of this area was mainly formed by the vertical tectonic movements occurred between Middle Miocene and Last Pleistocene; the intensity of erosion and sedimentation processes have been controlled by not only fluvial process but also lithologic properties of parent materials. The basement of the study area is mainly composed of peridotite-serpentine that erupted and spread on the bottom of the Tethys Ocean. Clay-rich calcareous sediments forming limestones were accumulated on the peridotite-serpentine. They were emerged from the Tethys oceans as the result of tectonic movement occurred at the end of the Mesozoic era. The sandstone-conglomerate terrain was formed on the depression areas in the north-western part of the present-day Sogut Mountains. The clayey and calcareous materials were accumulated in the neogene lake facies in the Burdur-Golhisar basins. The main fault line passing in the east of the Burdur basin was rejuvenated six times. Thus, the faulted topography and erosion surfaces especially on marl deposit were developed according to the base level of the Burdur Basin and Golhisar basins. The physical and chemical properties of the geologic parent materials have affected considerably soil formation and their physical and chemical traits. Namely, red Mediterranean soils (Alifsol/Luvisol) have developed along the cracks and bedding surfaces of limestones on the sloping area and on the bottom of the karstic depression. The flat land lying between Golhisar and Burdur Basins is the main spreading areas of chestnut soil (Mollisol). Rendzina soils have developed on the upper erosion surfaces on the marl deposit. The productive vegetation cover is found on the soft and inclined layered marl deposit, while poor vegetation cover is common on the compact and horizontally layered marl deposit. Sparse vegetation communities are seen on the exposed hard and partly weathered serpentine, whereas productive forest trees are found on the deeply weathered serpentine. At the same time, productive vegetation communities are common on the sandy soil developed on the sandstone and conglomerate. Vineyards, levanter and rose gardens are found on the dejection fan and dejection cones on the edges of the fault scarps in the Burdur Basin.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Neotectonic; Soil Formation; Faulted Topography; Burdur-Golhisar Basin